2016
DOI: 10.1007/s13593-016-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Crop-specific and single-species mycorrhizal inoculation is the best approach to improve crop growth in controlled environments

Abstract: Arbuscular mycorrhizal fungi are root symbionts that play a key role in crop growth. A systematic quantitative analysis of the response of crops to arbuscular mycorrhizal inoculation, however, remains to be done. Additionally, little is known regarding the role of mycorrhizal specificity and the diversity of the inoculum on crop growth. Therefore, we collected data from 115 inoculation studies, including 435 experiments. We then used meta-analysis to examine the effect of crop identity, arbuscular mycorrhizal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…In such cases, isolation of indigenous mycorrhizal strains for inoculum production, then large-scale reintroduction of these native fungi in the field could be a feasible solution for a useful AMF application [142]. It is worth mentioning that selection of specific AM taxa for particular crops is the best approach to improve crop growth, and there is no 'one-size-fits-all' AMF [143]. In controlled environments, application of a single AMF is more effective than using a mixture of different AM taxa [143].…”
Section: Challenges Of Amf Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, isolation of indigenous mycorrhizal strains for inoculum production, then large-scale reintroduction of these native fungi in the field could be a feasible solution for a useful AMF application [142]. It is worth mentioning that selection of specific AM taxa for particular crops is the best approach to improve crop growth, and there is no 'one-size-fits-all' AMF [143]. In controlled environments, application of a single AMF is more effective than using a mixture of different AM taxa [143].…”
Section: Challenges Of Amf Applicationmentioning
confidence: 99%
“…It is worth mentioning that selection of specific AM taxa for particular crops is the best approach to improve crop growth, and there is no 'one-size-fits-all' AMF [143]. In controlled environments, application of a single AMF is more effective than using a mixture of different AM taxa [143].…”
Section: Challenges Of Amf Applicationmentioning
confidence: 99%
“…These tripartite biotic interactions (involving antagonistic, protective, exclusive, or synergistic effects) are of particular interest with regard to crop plants, since they strongly influence the crop productivity. It is documented that under the field conditions the majority of crop plants establishes symbiotic association between their roots and arbuscular mycorrhizal fungi (AMF) being an inherent component of each agricultural ecosystem (Smith and Smith, 2011;Van Geel et al, 2016). In this endomycorrhizal relationship both partners benefit from one another.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, herbaceous plant species that co-occur in the same grasslands have been shown to harbor distinct AMF communities (Vandenkoornhuyse et al, 2003;Valyi et al, 2015; but see Honnay et al, 2017). A metaanalysis of 435 crop inoculation experiments also showed that specific combinations of AMF taxa and host plants were more beneficial for growth promotion as compared with others, suggesting a functional AMF-host plant specificity (Van Geel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%